KETERLIBATAN PENTAHELIX DALAM PENGELOLAAN BANK SAMPAH - Muhammad Daffa Rizqi Eko Putra; Santoso Tri Raharjo (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2023)
Abstract. A company's CSR program cannot be implemented alone, but requires the support of the involvement of various parties in order to achieve the expected goals. These various parties or stakeholders can consist of individuals, groups, or organizations as well as communities or governments; expected to contribute and be involved in the implementation of CSR programs. The involvement of various stakeholders is one of the key factors that need to be considered, considering the effectiveness and efficiency in achieving the program, as well as the sustainability of empowerment. There are at least 5 (five) categories of stakeholders who can be involved and collaborate in CSR programs, namely Academic, Business, Community, Government and Media (ABCGM). Each stakeholder plays a different role according to their respective capacities and abilities, as well as their respective authorities. The purpose of this research is to describe the involvement and collaboration of stakeholders in environmental management CSR programs, especially in the management of waste banks. A qualitative approach with a descriptive method is used to describe the involvement of stakeholders in the CSR program "Bank Garbage" Kompas Gramedia in RW 02 Kelurahan Gelora, by observing the involvement of five parties (pentahelix) or stakeholders in the program. The results showed that the involvement and cooperation of pentahelix in the CSR program was observed to support the implementation of the program and the achievement of the objectives of the CSR program for waste bank management. Each stakeholder has a different role, but collaborates with each other to achieve the expected goals. Awareness and openness of each stakeholder is the key to cooperate with each other, so that this becomes the basic capital for the sustainability of the program into the future. Keywords: Corporate social responsibility (CSR), pentahelix, collaboration, waste bank. Abstrak. Program CSR suatu perusahaan tidak dapat dilaksanakan sendiri, melainkan membutuhkan dukungan keterlibatan berbagai pihak agar mencapai tujuan yang diharapkan. Berbagai pihak atau stakeholders tersebut bisa terdiri dari individu, kelompok, maupun organisasi serta komunitas atau juga pemerintah; diharapkan dapat berkontribusi dan dilibatkan dalam pelaksanaan program CSR. Keterlibatan berbagai stakeholders merupakan salah satu faktor kunci yang perlu diperhatikan, mengingat efektivitas dan efisiensi dalam pencapaian program, serta sustainability pemberdayaan. Setidaknya terdapat 5 (lima) kategori stakeholders yang dapat dilibatkan dan berkolaborasi  dalam program-program CSR, yaitu Academic, Business, Community, Government and Media (ABCGM). Masing-masing stakeholders memainkan peran yang berbeda sesuai dengan kapasitas dan kemampuan, serta kewenangan masing-masing. Tujuan riset ini adalah menggambarkan bagaimana keterlibatan dan kolaborasi stakeholder dalam program CSR pengelolaan lingkungan khususnya dalam pengelolaan bank sampah. Pendekatan kualitatif dengan metode deskriptif digunakan untuk menggambarkan keterlibatan stakeholders dalam program CSR “Bank Sampah” Kompas Gramedia di RW 02 Kelurahan Gelora, dengan mengamati  keterlibatan lima pihak (pentahelix) atau stakeholder dalam program tersebut. Hasil penelitian menunjukkan bahwa keterlibatan dan kerjasama pentahelix dalam program CSR teramati mendukung terlaksananya program dan pencapaian tujuan program CSR pengelolaan bank sampah. Masing-masing stakeholder memiliki peranan yang berbeda, namun saling berkolaborasi untuk mencapai tujuan yang diharapkan. Kesadaran dan keterbukaan masing-masing stakeholder merupakan kunci saling bekerja sama, sehingga hal ini menjadi modal dasar pada keberlanjutan program ke masa depan. Kata Kunci: Corporate social responsibility (CSR), kolaborasi, pentahelix, bank sampah.